Alveolar Dynamics and Beyond – The Importance of Surfactant Protein C and Cholesterol in Lung Homeostasis and Fibrosis - Sehlmeyer, Kirsten; Ruwisch, Jannik; Roldan, Nuria; Lopez-Rodriguez, Elena (Frontiers in Physiology, 2020)
Surfactant protein C (SP-C) is an important player in enhancing the interfacial adsorption of lung surfactant lipid films to the alveolar air-liquid interface. Doing so, surface tension drops drown enough to stabilize alveoli and the lung, reducing the work of breathing. In addition, it has been shown that SP-C counteracts the deleterious effect of high amounts of cholesterol in the surfactant lipid films. Even though the molecular mechanism is not known, there are evidences that this two molecules may interplay with each other in order to keep the proper function of the lung. Cholesterol is also known to change the biophysical properties of biological membranes, and activate the inflammasome pathways in the lung. This review focus in the involvement of SP-C and cholesterol in the development of lung fibrosis and the potential pathways where impairment of both lead to aberrant lung repair, and therefore impaired alveolar dynamics. From molecular to cellular mechanisms to evidences in animals models and human diseases. Taken all together, we also revised the latest results point at a potential SP-C/cholesterol axis as target for the treatment of lung fibrosis.